2021
DOI: 10.3389/fpsyt.2021.744806
|View full text |Cite
|
Sign up to set email alerts
|

A Biopsychosocial-Ecological Framework for Family-Framed Dementia Care

Abstract: The biopsychosocial model has been applied through collaborative care dementia models to the diagnosis, symptom management, and treatment of dementia with a focus specifically on the person with dementia. Because individuals with dementia are increasingly dependent upon others particularly as the illness advances, dementia care requires the involvement and commitment of others, usually family, along with support from community-based resources. Hence, the quality and effectiveness of a person's dementia care ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…As found in this research, dyads benefit from personalised facilitation to meet their complex and changing needs. This aligns with the broadly accepted recommendations for the personalised use of music for people with dementia ( 52 , 53 ) and the need to consider family dynamics within family-centred approaches to dementia care ( 54 , 55 ). Due to the heterogeneity of dyads’ contexts, music therapists need to build an understanding of dyads’ musical worlds ( 15 ) to provide the best individualised care.…”
Section: Discussionsupporting
confidence: 71%
“…As found in this research, dyads benefit from personalised facilitation to meet their complex and changing needs. This aligns with the broadly accepted recommendations for the personalised use of music for people with dementia ( 52 , 53 ) and the need to consider family dynamics within family-centred approaches to dementia care ( 54 , 55 ). Due to the heterogeneity of dyads’ contexts, music therapists need to build an understanding of dyads’ musical worlds ( 15 ) to provide the best individualised care.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the present review demonstrated that carers needed to know their roles as carers. Similarly, previous reviews reported various roles of carers throughout the trajectory of care provision, for example, care provider, communicator and interpreter 35 86. Therefore, informal carers should be provided with information related to their caring roles,87 and it is essential to develop affordable educational resources for carers, especially in developing countries.…”
Section: Discussionmentioning
confidence: 95%
“…Podgorski et al. (2021) has more specifically developed a biopsychosocial–ecological framework to more broadly guide family‐framed dementia care from a service perspective. This framework informs a path to increasing adoption of systemic congruent ideas in dementia services, rather than specifically focusing on therapy guidance.…”
Section: Literature Reviewmentioning
confidence: 99%